Transformation Of Groundnut - Arachis Hypogea L. Var. Gg20 With The Cox Gene-An Attempt To Develop Salinity Tolerance - ASHUTOSH VADAWALE,; RITU MIHANI,; ASHA MATHEW,; PUSHPA ROBIN, (International Journal of Pharma and Bio Sciences, 2012)
Salinity, is one of the most serious environmental factors limiting the productivity of crop plants and agricultural production world-wide. An attempt was made to develop salinity tolerance in Groundnut-Arachis hypogea l. var GG20 through Agrobacterium mediated transformation with the cox gene for synthesis of Glycine betaine. Agrobacterium tumefaciens LBA 4404 with binary vector pHS724 containing the cox gene was co-cultivated with different groundnut explants for infection and transformation. Various factors like explant types and co-cultivation period affecting transformation and concentration of kanamycine in selection medium were studied. The successful transformants were confirmed through phenotypic expression as well as through the expression of GUS gene (uidA gene) in the regenerated plants.